Aktualisasi Tujuan Pendidikan Islam Dari Perspektif Imam Al-Ghazali - Divani Raniadi (Nizham Jurnal Studi Keislaman, 2023)
The general objective of this analysis is to identify Imam Al-Ghazali's definition of Islamic religious education. The specific objective of this analysis is to understand al-Ghazali's views on science and Islamic educational theory. Study. The literature review method is used in this literature research, which includes theories related to the conditions of analysis. This structure of analysis conveys that happiness in the world and beyond can be obtained from knowledge. When compared to other creatures, science will change humans to create noble and dignified individuals. Al-Ghazali's views on the idea of Islamic education. First, the educational aspects of Islamic education, namely a) the Qur'an and Hadith are used as the main educational foundation because the main goal of education is the happiness of the world and the hereafter; b) An educator must have the initial goal of bringing students closer to God, being an example for them, and proficient in teaching; c) Students must study with the intention of getting closer to Allah, refraining from committing crimes because insight is pure and does not need to be conveyed to the immoral, respecting mentors, and diligently seeking knowledge through studying the knowledge conveyed; d) The study program as a means of teaching must be balanced through the individual needs of students; e) Students must avoid negative friendships because negative areas will have an impact on their development, especially in the family, school or community environment. Second, the development of educational organizations that incorporate elements of Islamic education into their study programs, such as midday prayers, reading the holy verses, and congregational prayers mark the implementation of educational values from al-Ghazali's point of view in the modern era.